St Kentigern’s Church, Lanark - Davidson, John M (Proceedings of the Society of Antiquaries of Scotland, 1912)
There is only one church dedicated to him under his own proper name though there are many others dedicated to him under the name of St Mungo. The church of St Kentigern lies immediately to the south-east of Lanark. it was dedicated to the monastery of Dryburgh by a charter of King David I granted between the years 1150 and 1153. An account of various donations to the parish church is given along with a description of the ruins. The church bell was removed to the town steeple when St Kentigern's Church was disused for public worship.